The effect of process parameters on mechanical characteristics of specimens obtained via DLP additive manufacturing technology. (2023) - Brighenti, Roberto; Marsavina, Liviu; Marghitas, Mihai P.; Montanari, Matteo; Spagnoli, Andrea; Tatar, Farzad
Abstract: Digital Light Process (DLP) is one of the Additive Manufacturing (AM) methods to produce three-dimensional (3D) polymeric components with high dimensional stability. The technique is based on light-induced polymerization, consisting in spreading the light of a suitable wavelength in a spatially controlled area according to the component's digital model. Starting from a liquid monomer solution, a 3D solid polymeric object is created. The mechanical and fracture properties of such components are highly influenced by the process parameters which must be carefully considered when load bearing parts have to be produced by AM. This paper investigates the effect of the DLP process parameters on tensile properties using dog bone specimens and fracture toughness determined by using Single Edge Notch Specimens loaded in three-point bending. Five different process parameters were considered by testing six specimens; for each of them, the influence of the printing orientation on the fracture toughness of UV-sensitive resin "translucent green" (curing UV light wavelength 405 nm) is considered. Among the various parameters, the study considers also the post-processing effects on the fracture toughness.